Flying and handling qualities of a fly-by-wire blended-wing-body civil transport aircraft - de Castro, Helena V. (Cranfield University, 2003)
The blended-wing-body (BWB) configuration appears as a promising contender for the next generation of large transport aircraft. The idea of blending the wing with the fuselage and eliminating the tail is not new, it has long been known that tailless aircraft can suffer from stability and control problems that must be addressed early in the design. This thesis is concerned with identifying and then evaluating the flight dynamics, stability, flight controls and handling qualities of a generic BWB large transport aircraft concept. Longitudinal and lateral-directional static and dynamic stability analysis using aerodynamic data representative of different BWB configurations enabled a better understanding of the BWB aircraft characteristics and identification of the mechanisms that influence its behaviour. The static stability studies revealed that there is limited control power both for the longitudinal and lateral-directional motion. The solution for the longitudinal problem is to limit the static margins to small values around the neutral point, and even to use negative static margins. However, for the directional control problem the solution is to investigate alternative ways of generating directional control power. Additional investigation uncovered dynamic instability due to the low and negative longitudinal and directional static stability. Furthermore, adverse roll and yaw responses were found to aileron inputs. The implementation of a pitch rate command/attitude hold flight control system (FCS) improved the longitudinal basic BWB characteristics to satisfactory levels, or Level 1, flying and handling qualities (FHQ). Although the lateral-directional command and stability FCS also improved the BWB flying and handling qualities it was demonstrated that Level 1 was not achieved for all flight conditions due to limited directional control power. The possibility to use the conventional FHQs criteria and requirements for FCS design and FHQs assessment on BWB configurations was also investigated. Hence, a limited set of simulation trials were undertaken using an augmented BWB configuration. The longitudinal Bandwidth/Phase delay/Gibson dropback criteria, as suggested by the military standards, together with the Generic Control Anticipation Parameter (GCAP) proved possible to use to assess flying and handling qualities of BWB aircraft. For the lateral-directional motion the MIL-F-8785C criteria were used. Although it is possible to assess the FHQ of BWB configuartions using these criteria, more research is recommended specifically on the lateral-directional FHQs criteria and requirements of highly augmented large transport aircraft.
Keywords: Tailless aircraft; Aircraft handling; Blended wing body; Fly by wire; Aircraft stability